Segurança do paciente e detecção precoce de Sepse: WebQuest para Enfermeiros - Laurenti, Thaís Cristina (Universidade Federal de São Carlos, 2018)
Sepsis is a subject of significant relevance due to the constant increase in its incidence. It is estimated that around 600,000 new cases occur annually in Brazil and 17 million worldwide. Therefore, it is considered a challenge for public health. To perform the early detection of sepsis, it is essential that the nursing team has knowledge about the content and is competent to identify the clinical manifestations and, consequently, to execute the pertinent interventions. The aim of the research was to develop a digital learning environment using the WebQuest methodology on sepsis and to perform the evaluation of appearance and content with specialist nurses in the area. It is an applied research of technological development with quantitative approach. For the development of WebQuest the following steps were covered: Conception and Planning; Development; Implementation and Evaluation of the WebQuest by the specialist nurses and the Health Surveillance Sector. A total of ten nurses took part in the research, of which eight specialists were distributed in the areas of Sepsis, Patient Safety and Nursing Informatics. And the other two nurses worked in the Health Surveillance Sector of a university hospital located in the interior of the state of São Paulo. WebQuest was evaluated positively in relation to its objectives, content, structure and presentation, activities and relevance, standing out as an effective strategy for the professional qualification in the nursing area. The results obtained from the evaluations of specialists and nurses of the Health Surveillance Sector contributed to assist in the adequacy of WebQuest in order to make it available to the target audience in the future. It is hoped that this material contributes to the development of innovative educational strategies through the use of active methodologies, aiming to provide quality and safety in health care, especially with regard to the topic of sepsis.
Patient safety and early Sepsis screening: WebQuest for Nurses
Keywords: Sepse; Informática em enfermagem; Segurança do paciente; WebQuest; Sepsis; Nursing informatics; Patient safety; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM MEDICO-CIRURGICA